2000
DOI: 10.1080/10715760000301131
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the antioxidant properties of non steroidal anti-inflammatory drugs by chemiluminescence and electron spin resonance (ESR)

Abstract: The NSAIDs possess variable degrees of antioxidant activities, linked to their ability to react with HOCl, lipid peroxides or ONOO-. These antioxidant activities could offer interesting targeted side-effects in the treatment of joint inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 36 publications
(20 reference statements)
2
35
0
Order By: Relevance
“…Nimesulide, like some classical NSAIDs exhibits a considerable degree of anti-infl ammatory activity as a consequence of various inhibitory effects on polymorphonuclear neutrophil leucocytes (PMNs) (Dallegri et al, 1990(Dallegri et al, , 1992a(Dallegri et al, , 1992bOttonello et al, 1992Ottonello et al, , 1993Ottonello et al, , 1995Ottonello et al, , 1999Capecchi et al, 1993;Verhoeven et al, 1993;Bevilacqua et al, 1994;Dapino et al, 1994;Tool and Verhoeven, 1995;Bennett and Villa, 2000;Bennett, 2001;Mouithys-Mickalad et al, 2000;Nakatani et al, 2001;Gomez-Gaviro et al, 2002;Bravo-Cuellar et al, 2003;Kimura et al, 2003;Rainsford et al, 2005). These effects are, in some cases, relatively potent compared with the activities of other NSAIDs, and occur within the drug concentrations in plasma or synovial fl uids encountered during therapy with the drug Bennett and Villa, 2000;Bennett, 2001).…”
Section: Cox-2 and Anti-infl Ammatory Activitymentioning
confidence: 97%
“…Nimesulide, like some classical NSAIDs exhibits a considerable degree of anti-infl ammatory activity as a consequence of various inhibitory effects on polymorphonuclear neutrophil leucocytes (PMNs) (Dallegri et al, 1990(Dallegri et al, , 1992a(Dallegri et al, , 1992bOttonello et al, 1992Ottonello et al, , 1993Ottonello et al, , 1995Ottonello et al, , 1999Capecchi et al, 1993;Verhoeven et al, 1993;Bevilacqua et al, 1994;Dapino et al, 1994;Tool and Verhoeven, 1995;Bennett and Villa, 2000;Bennett, 2001;Mouithys-Mickalad et al, 2000;Nakatani et al, 2001;Gomez-Gaviro et al, 2002;Bravo-Cuellar et al, 2003;Kimura et al, 2003;Rainsford et al, 2005). These effects are, in some cases, relatively potent compared with the activities of other NSAIDs, and occur within the drug concentrations in plasma or synovial fl uids encountered during therapy with the drug Bennett and Villa, 2000;Bennett, 2001).…”
Section: Cox-2 and Anti-infl Ammatory Activitymentioning
confidence: 97%
“…Most related studies have used human PMN (Neal et al 1987;Parij et al 1998;Mouithys-Mickalad et al 2000;Abdullah et al 2001) in which a number of non-steroidal anti-inflammatory drugs (NSAIDs) were found effective in modulating PMN oxidative activity (Van Dyke et al 1982;Neumuller and Tohidast-Akrad 1994). The direct effects of NSAIDs on ex-vivo isolated equine neutrophils have not been fully investigated, especially in relation to their oxidative activity.…”
Section: Introductionmentioning
confidence: 96%
“…Chemiluminescence measures the total oxidant activity produced by the reaction of the oxidant species with the chemiluminescent probe. The possible reaction between probe and drug is not excluded, leading to the attribution of a pro-oxidant effect [16,17]. Diclofenac, isoxicam, zomepirac and valeryl aalycilate exhibited the same pronounced concentration-dependent O 2 .À scavenging activities (Figure 2a and 2b).…”
Section: O 2 à Radical Scavenging Effectmentioning
confidence: 86%